KAJIAN KESIAPAN PENERAPAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) BERDASARKAN PERSEPSI PESERTA DIDIK DI SMK KARSA MULYA PALANGKA RAYA - Tarita Aprilani Sitinjak; Ni Putu Diah Agustin Permanasuri; Whendy Trissan; Riris Krisdempuan Nadeak; Bonardo Sadatuah Siallagan (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2023)
Readiness to implement the independent curriculum implementation is the main thing that supports the success of the curriculum. The Pancasila Learner Profile Strengthening Project (P5) is part of the newly implemented Merdeka curriculum at SMK Karsa Mulya. This study aims to determine the school's readiness based on students' perceptions in implementing P5. Questionnaires were distributed to 75 learners and the scores from the questionnaires filled in by respondents were analysed and converted into qualitative criteria, referring to the Benchmark Approach (PAP) conversion. The variables studied were knowledge, school infrastructure and learner characteristics. The results of the analysis show a value of 4.07 referring to the conversion of the Benchmark Approach (PAP) then X = 4.08 is on a scale of 4 because 3.4 < X